Pengaruh Literasi Digital Guru dan Keaktivan Komunitas Belajar Terhadap Kompetensi Profesional Guru Sekolah Dasar Negeri - Arbain, Arbain; Nurkolis, Nurkolis; Yuliejantiningsih, Yovitha (PGRI Kota Semarang, 2024)
Low digital literacy and teacher activity when carrying out the teaching and learning process can result in low student learning outcomes. Therefore, the issue of digital literacy and teacher activity in the learning process in schools must be given more attention so that the hope is that schools can provide evidence that teachers' professional competence is running smoothly. The formulation of the research problem is: 1) is there an influence of school teachers' digital literacy on teacher professional competence, 2) is there an influence of learning community activity on teacher professional competence, 3) is there an influence of teacher digital literacy and learning community activity on teacher professional competence.This research approach is quantitative which emphasizes analysis of numerical data (numbers) processed using statistical methods. Place: This research was conducted at an elementary school in Singorojo District, Kendal Regency. This research was carried out from March to Aprli 2024. The research sample used was a population of 113. The data collection technique used in this research was a questionnaire. Data analysis includes descriptive analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test and hypothesis test.The research results show that (1) there is an influence of digital literacy on teacher professional competence of 72.2%, (2) there is an influence of learning community activity on teacher professional competence of 44.8%, (3) there is an influence of teacher digital literacy and community activity learning together on teacher professional competence was 77.8%.The conclusion is that there is an influence of teacher digital literacy and learning community activity on the professional competence of teachers in elementary schools in Singorojo District, Kendal Regency. Research suggestions so that school principals can support learning community activities and teacher digital literacy.